KETEPATAN PASAR MODAL DALAM MEMPREDIKSI KONDISI EKONOMI (Study Empiris di Bursa Efek Indonesia tahun 2013-2017) - Nuansa Risky; Maslichah Maslichah; Muhammad Cholid Mawardi (Universitas Islam Malang, 2018)
ABSTRACTThis study examines the accuracy of the Indonesian stock market in predictingIndonesia's economic conditions in the future. Economic conditions arerepresented by changes in the level of Gross Domestic Product and Inflation ratesfor the monthly period. Changes in the world economy are represented bychanges in the United States S & P 500 stock index, and Japan Nikkei 225 stockindex. Research time covers 2013 to 2017. The results of the f test show that allvariables affect the returns IHSG, while the results of the t test shows thatInflation and Gross Domestic Product have a negative effect and significant onreturn IHSG stock returns and the S & P 500 Index Nikkei 225 Index has apositive and significant effect on return IHSG . This shows that the Indonesianstock market is unable to be used to predict Indonesia's future economicconditions, but is more influenced by world economic conditions reflected inchanges in the US and Japanese stock markets.Keywords : Return IHSG,Gross Domestic Product , S&P 500 stock index andNikkei 225 stock index